2022
DOI: 10.47989/colis2214
|View full text |Cite
|
Sign up to set email alerts
|

Understanding information-seeking achievement emotions - exploring a cognitive appraisal theory framework

Abstract: Given the limited body of literature on information-seeking emotions in library and information science research in general and relative to appraisal theories in an educational context, the findings of this paper will make a valuable conceptual and theoretical contribution to the field. The paper explores a proposed appraisal theory framework for understanding the information-seeking emotions of higher education students in learning and achieving information-seeking skills. Studying this process is crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This study makes a valuable contribution to the limited body of literature on emotions identified by researchers in information-seeking behaviour research in general (e.g. Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015b) and regarding teacher students in particular (Dahlqvist, 2021a, b and 2022). Increased knowledge of the fundamentally important role emotions play in formal and higher education contexts, especially an in-depth understanding of the qualitative nuances and variations of primary teacher students' experienced appraisals and emotions in the process of achieving information-seeking skills.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This study makes a valuable contribution to the limited body of literature on emotions identified by researchers in information-seeking behaviour research in general (e.g. Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015b) and regarding teacher students in particular (Dahlqvist, 2021a, b and 2022). Increased knowledge of the fundamentally important role emotions play in formal and higher education contexts, especially an in-depth understanding of the qualitative nuances and variations of primary teacher students' experienced appraisals and emotions in the process of achieving information-seeking skills.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is still a limited body of literature on emotions, as noted by several researchers (e.g. Dahlqvist, 2021a, b and 2022; Krakowska, 2020; Lopatovska and Arapakis, 2011; Savolainen, 2015a; Savolainen, 2015b). Despite this lack of research, there are several valuable LIS and IB contributions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations